Assessing Research Activity and Capacity of Community-Based Organizations: Refinement of the CREAT Instrument Using the Delphi Method. - Humphries, Debbie; Ma, Maria; Collins, Nicole; Ray, Natasha; Wat, Eric; Bazelon, Jill; Pettinelli, Jim; Fiellin, David A. (Journal of Urban Health, 2019)
Community-based organizations (CBOs) are essential partners in community-engaged research, yet little is known about their research capacity. Community experts and organizations bring unique knowledge of the community to research partnerships, but standard validated measures of CBO research capacity do not yet exist. We report here on the refinement through a structured Delphi panel of a previously developed and piloted framework of CBO research capacity and an accompanying instrument, the Community REsearch Activity Assessment Tool (CREAT). A Delphi panel composed of twenty-three experts recruited from community (52%) and academic researchers (48%) from around the USA participated in five rounds of review to establish consensus regarding framework domains, operational definitions, and tool items. Panelists rated the importance of items on a 5-point Likert scale and assessed for the inclusion and language of items. Initial rounds of review began with reviewing the framework and definitions, with subsequent rounds including review of the full instrument. Concluding rounds brought back items that had not yet reached consensus for additional review. Median response values (MRV) and intra-quartile ranges (IQR) were calculated for each Likert item. Items with an MRV > 3.5 were deemed as having reached consensus and were retained. Language changes were made for items with MRV > 2.0 and < 3.5 and an IQR > 1.5. Items with MRV < 2.0 were excluded from the final tool. Panelist response rate was high (> 75%). Consensus was achieved for the inclusion of all domains, subdomains and operational definitions except "evidence-based practices." Extensive changes to the CREAT instrument were made for clarification, to provide additional detail and to ensure applicability for CBOs. The CREAT framework and tool was refined through input from community and academic researchers. Availability of a validated tool to assess research capacity of CBOs will support targeted research capacity building for community organizations and partners, thus strengthening collaborations.